2020
DOI: 10.1186/s12885-020-06951-w
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of the T2-FLAIR mismatch sign in grade II and III gliomas: a population-based study

Abstract: Background: The T2-FLAIR mismatch sign is an imaging finding highly suggestive of isocitrate dehydrogenase mutated (IDH-mut) 1p19q non-codeleted (non-codel) gliomas (astrocytomas). In previous studies, it has shown excellent specificity but limited sensitivity for IDH-mut astrocytomas. Whether the mismatch sign is a marker of a clinically relevant subtype of IDH-mut astrocytomas is unknown. Methods: We included histopathologically verified supratentorial lower-grade gliomas (LGG) WHO grade II-III retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 34 publications
3
39
1
Order By: Relevance
“… 14–18 , 20 , 21 A study tried to amass the two independent patient groups (each retrospective and prospective manners). 19 The total included study population was 1342 with individual cohorts ranging from 59 to 408 patients. The patients had mean ages of 43–57 years.…”
Section: Resultsmentioning
confidence: 99%
“… 14–18 , 20 , 21 A study tried to amass the two independent patient groups (each retrospective and prospective manners). 19 The total included study population was 1342 with individual cohorts ranging from 59 to 408 patients. The patients had mean ages of 43–57 years.…”
Section: Resultsmentioning
confidence: 99%
“…We used the QUADAS-2 tool to identify possible risk of bias within the included studies. The assessment revealed low risk of bias and applicability concerns in all studies, except three [ 9 , 10 , 13 ], where the risk was high in regard to the index test, due to the assessment of the MR images by a neurologist in one study and a neurosurgeon in two studies. A high applicability concern was found in one study regarding its index test, since there was no mentioning about the observers being blinded.…”
Section: Resultsmentioning
confidence: 96%
“…The relatively low diagnostic accuracy presented by the study, might be due to not relying on the strict imaging criteria for the mismatch sign identification that Patel et al first suggested [ 21 ]. In another study, apart from the diagnostic accuracy of the mismatch sign, Corell et al [ 13 ] investigated its relation to methylation profiles. They confirmed its high specificity and low sensitivity, while methylation analysis indicated that the sign does not compromise a separate subentity.…”
Section: Discussionmentioning
confidence: 99%
“…Throckmorton et al claimed that broadening the criteria to include T2-heterogeneous LGG lesions increased the sensitivity of the T2–FLAIR mismatch sign by 30% [ 26 ]. According to a population-based study focusing on LGGs by Correl et al, the sensitivity and specificity of the mismatch sign for IDH mutation detection were 26.4% and 97.6%, respectively [ 27 ]. Our study extended the spectrum of glioma to include patients with high-grade glioma (HGG).…”
Section: Discussionmentioning
confidence: 99%